2010
DOI: 10.1038/ijo.2010.25
|View full text |Cite
|
Sign up to set email alerts
|

Western diet increases wheel running in mice selectively bred for high voluntary wheel running

Abstract: Objective: Mice from a long-term selective breeding experiment for high voluntary wheel running offer a unique model to examine the contributions of genetic and environmental factors in determining the aspects of behavior and metabolism relevant to body-weight regulation and obesity. Starting with generation 16 and continuing through to generation 52, mice from the four replicate high runner (HR) lines have run 2.5-3-fold more revolutions per day as compared with four non-selected control (C) lines, but the na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 59 publications
2
68
0
Order By: Relevance
“…In contrast, several findings in the Myh4 knockout strain do not closely match data from mini-muscle mice. For example, mini-muscle mice have longer tibiafibulae (Kelly et al 2006), eat more food per gram of body mass (Meek et al 2010), have disorganized muscle fibers in certain muscle regions (Guderley et al 2006(Guderley et al , 2008, and have reduced contractile speed (Syme et al 2005;McGillivray et al 2009), whereas none of those alterations have been reported in the Myh4 knockout mice. Some of the differences between the mice may be attributable to context (specific muscle studied, age, sex, rearing environment), while others may be due to the different types of mutations (null in the knockout and likely hypomorphic in the minimuscle mice.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, several findings in the Myh4 knockout strain do not closely match data from mini-muscle mice. For example, mini-muscle mice have longer tibiafibulae (Kelly et al 2006), eat more food per gram of body mass (Meek et al 2010), have disorganized muscle fibers in certain muscle regions (Guderley et al 2006(Guderley et al , 2008, and have reduced contractile speed (Syme et al 2005;McGillivray et al 2009), whereas none of those alterations have been reported in the Myh4 knockout mice. Some of the differences between the mice may be attributable to context (specific muscle studied, age, sex, rearing environment), while others may be due to the different types of mutations (null in the knockout and likely hypomorphic in the minimuscle mice.…”
Section: Discussionmentioning
confidence: 96%
“…Adult mice were fed an obesity-inducing diet (Table S2) that mimics the Western diet linked to risk of cardiovascular diseases in humans (13)(14)(15), and immediately started on a therapeutic regimen of ShK-186 or vehicle. ShK-186's durable pharmacological activity in rodents and nonhuman primates (16) allowed us to administer the peptide every other day by s.c. injection.…”
Section: Resultsmentioning
confidence: 99%
“…In this model, mice fed an obesity-inducing diet rich in both fat and fructose (Tables S2 and S3) gain significant weight and adiposity, and develop insulin resistance within 6-8 wk (12)(13)(14)(15). As a Kv1.3 blocker we chose ShK-186 because of its picomolar potency (IC 50 69 pM), >100-fold selectivity over closely related channels, weak immunogenicity, and excellent safety profile in rodents and nonhuman primates (16)(17)(18)(19)(20)(21).…”
mentioning
confidence: 99%
“…in hunger, satiety or dietary adherence (Schoeller, 2009). Moreover, alterations in specific dietary components can have effects that go far beyond their effects on energy intake [Jebb (Jebb, 2007) and references therein] (Meek et al, 2010). Hence, prospective use of the energy balance equation can be a risky proposition with respect to bringing about reductions in human body fat (Schoeller, 2009).…”
Section: Dee and Its Componentsmentioning
confidence: 99%